Effect of nickel on the organization of actin filaments in Arabidopsis thaliana primary root cells - Horiunova, I. I.; Krasylenko, Yu. A.; Yemets, A. I.; Blume, Ya. B. (Reports of the National Academy of Sciences of Ukraine, 2016)
The influence of one of the most toxic heavy metals — nickel (Ni2+) — on the organization of actin filaments (microfilaments) of different types of Arabidopsis thaliana (L.) root cells is studied in living cells by the laser scanning microscopy. To visualize microfilaments, the A. thaliana line expressing chimeric gene gfp-fabd2 was used. Ni2+ leads to a significant inhibition of the growth of the main root and disturbs its morphology, causing the swelling of epidermal cells and inducing a large number of abnormally long root hairs. For the first time, it has been shown that Ni2+ disturbs the organization of actin filaments in cells, leading to morphological changes of a root as the main organ, being the first exposed to the intoxication by soil pollutants. It is found that the most sensitive to its action are actin filaments of epidermal cells of all growth zones of A. thaliana root.